Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1155/2018/1275720
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Thrombocytopenia May Predict Poor Surgical Outcome after Extended Hepatectomy

Abstract: Background It is a novel idea that platelet counts may be associated with postoperative outcome following liver surgery. This may help in planning an extended hepatectomy (EH), which is a surgical procedure with high morbidity and mortality. Aim The aim of this study was to evaluate the predictive potential of platelet counts on the outcome of EH in patients without portal hypertension, splenomegaly, or cirrhosis. Methods A series of 213 consecutive patients underwent EH (resection of ≥ five liver segments) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
1
6
1
Order By: Relevance
“…32 Patients with thrombocytopenia (100 x 10 9 /L or 150 x 10 9 /L) undergoing liver transplantation have increased morbidity and mortality. 33,34 In a cohort of 234 consecutive adult-to-adult living donor liver transplantation recipients, patients with an immediate postoperative low platelet level α≤ 68 X 10 3 /μL had higher rates of early allograft dysfunction (22.6% vs. 7.0%) and severe complications (22.6% vs. 10.9%) compared to those with a platelet level > 68 X 10 3 /μL. 34 One-, three-, and five-year patient survival and graft survival rates of patients with platelet counts < 60 X 10 9 /L on postoperative day 5 are lower than for patients with platelet counts ≥ 60 X 10 9 /L.…”
Section: Predictor Of Hepatic Decompensation After Liver Resection Anmentioning
confidence: 99%
“…32 Patients with thrombocytopenia (100 x 10 9 /L or 150 x 10 9 /L) undergoing liver transplantation have increased morbidity and mortality. 33,34 In a cohort of 234 consecutive adult-to-adult living donor liver transplantation recipients, patients with an immediate postoperative low platelet level α≤ 68 X 10 3 /μL had higher rates of early allograft dysfunction (22.6% vs. 7.0%) and severe complications (22.6% vs. 10.9%) compared to those with a platelet level > 68 X 10 3 /μL. 34 One-, three-, and five-year patient survival and graft survival rates of patients with platelet counts < 60 X 10 9 /L on postoperative day 5 are lower than for patients with platelet counts ≥ 60 X 10 9 /L.…”
Section: Predictor Of Hepatic Decompensation After Liver Resection Anmentioning
confidence: 99%
“…These results are, however, contrary to the existing literature evaluating the effect of preoperative platelet count on PHLF. [ 13 15 ] For instance, Maithel et al [ 13 ] reported in 231 cirrhotic patients that a platelet count <150 (G/l) constituted a risk factor for PHLF (reconstituted odds ratio: 7.33, 95% CI: 3.04–17.65), [ 8 ] as defined by a peak bilirubin >7 (mg/dl) or ascites. Tomimaru et al [ 14 ] also described in 277 cirrhotic patients that a platelet count <150 (G/l) predicted the occurrence of PHLF (reconstituted odds ratio: 3.81, 95% CI: 1.39–10.48), [ 8 ] as defined by the ISGLS definition.…”
Section: Discussionmentioning
confidence: 99%
“…Tomimaru et al [ 14 ] also described in 277 cirrhotic patients that a platelet count <150 (G/l) predicted the occurrence of PHLF (reconstituted odds ratio: 3.81, 95% CI: 1.39–10.48), [ 8 ] as defined by the ISGLS definition. Further, Golriz et al [ 15 ] recently reported in 231 cirrhotic patients undergoing extended hepatectomy (>4 liver segments) that a preoperative platelet count <150 (G/l) was an independent predictor of PHLF (odds ratio: 4.4, 95% CI: 1.3–15.0), as defined by the ISGLS definition.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, improved hepatic resection techniques and expanding indications have increased the use of extensive liver resection, leading to a higher risk of PHLF. Single-center studies report PHLF risk ranging between 25.8% and 35.3%, and the severe PHLF ranged between 11.3% and 28% [20][21][22][23]. Due to the large tumor diameters and major vascular invasion, approximately 62-80% of patients with huge HCC patients undergo major or extensive liver resection leading to morbidity and mortality rates ranging between 10.9-43.6% and 4.2-18.1% [24][25][26][27], respectively.…”
Section: Discussionmentioning
confidence: 99%